A Transparent, Wearable Fluorescent Mouthguard for High‐Sensitive Visualization and Accurate Localization of Hidden Dental Lesion Sites. Issue 21 (2nd April 2020) - Li, Xuemeng; Luo, Chongdai; Fu, Quanying; Zhou, Cuiping; Ruelas, Marina; Wang, Yingshuting; He, Jinxu; Wang, Yangyang; Zhang, Yu Shrike; Zhou, Jianhua
Abstract: Accurate detection and early diagnosis of oral diseases such as dental caries and periodontitis, can be potentially achieved by detecting the secretion of volatile sulfur compounds (VSCs) in oral cavities. Current diagnostic approaches for VSCs can detect the existence and concentrations, yet are not capable of locating the dental lesion sites. Herein, the development of a unique approach for accurately locating dental lesion sites using a fluorescent mouthguard consisting of the zinc oxide–poly(dimethylsiloxane) (ZnO‐PDMS) nanocomposite to detect the local release of VSCs is reported. The ZnO‐PDMS mouthguard displays a highly sensitive and selective response to VSCs, and exhibits high fluorescent stability, good biocompatibility, and low biological toxicity in normal physiological environments. Then, the wearable ZnO‐PDMS mouthguard is demonstrated to be able to identify the precise locations of lesion sites in human subjects. Combined with image analysis, the mouthguards successfully uncover the precise locations of dental caries, allowing convenient screening of hidden dental lesion sites that are oftentimes omitted by dentists. Due to low cost, long‐term stability, and good patient compliance, the proposed wearable mouthguard is suitable for large‐scale production and enables widely applicable, preliminary yet accurate screening of dental lesions prior to dental clinics and routine physical examinations. Abstract : Preliminary yet accurate diagnosis of dental caries and periodontitis is significant for protecting oral health. A wearable mouthguard of fluorescent zinc oxide–poly(dimethylsiloxane) is developed to accurately locate both obvious and hidden dental lesion sites by detecting the local release of volatile sulfur compounds, which is promising for large‐scale screening of potential dental diseases before time‐consuming and expensive in‐dentistry examinations.